Ensuring privacy in telemedicine: Ethical and clinical challenges. (April 2023) - Mishkin, Adrienne D; Zabinski, Jeffrey S; Holt, Grayson; Appelbaum, Paul S
Data privacy in telemedicine has been extensively considered and reviewed in the literature, such as explorations of consent, who can access information, and the security of electronic systems. However, privacy breaches are also a potential concern in the physical setting and surroundings of the patient. Here we review clinical situations in which there is unanticipated loss of privacy, as well as potential physical and psychological safety concerns for the patient and others when privacy is limited. We identify ethical concerns and explore the challenges of supporting full true autonomous decision-making in this situation. We close with preliminary recommendations at the patient, clinician, and systems levels to help ensure privacy is maintained.